Effect of extent and rate of wilting on nitrogen components of grass silage. (17th November 2012) - Edmunds, B.; Spiekers, H.; Südekum, K.‐H.; Nussbaum, H.; Schwarz, F. J.; Bennett, R.
Abstract Wilting grass prior to ensiling generally increases the dry matter (DM) intake but the effect of wilting on animal performance is still poorly understood. There is a need to improve understanding of the effects of wilting on the nutritional components and chemical composition of grass silage. This study focused on the effects of the extent and rate of wilting on N components of grass silage. Meadow grass was wilted to four DM contents (200, 350, 500, 650 g kg−1) at two different rates (fast, slow), creating a total of eight silages. Crude protein (CP) fractions were measured using the Cornell Net Carbohydrate and Protein System. Utilizable CP at the duodenum (uCP), a measure of feed protein value, was estimated using the modified Hohenheim gas test. Ruminally insoluble, undegraded feed CP (RUP) was measured using an in situ technique. Amino acid (AA) composition prior to and after rumen incubation was also investigated. Utilizable CP at the duodenum, RUP and true protein fractions B2 and B3 were increased by rapid wilting and high DM content (DM > 500 g kg−1), although the increase with DM was only mild for uCP, probably due to lower ME content in the DM‐650 silages. Non‐protein‐N decreased with increasing DM and rapid wilting. The higher RUP content from both DM‐650 silages leads to a higher total AA content after rumen incubation. Treatment also influenced the AA composition of the ensiled material, but the AA composition after rumen incubation was similar across treatments. Rapid and extensive wilting (DM > 500 g kg−1) improved protein value and reduced CP degradability. Increased uCP may result in higher milk protein yield, while reduced degradability may reduce N lost from urinary excretion. The primary effect of wilting on post‐ruminal AA supply from RUP appeared to be quantitative, rather than qualitative.